Celebrating the National Unity in the Kingdom of Serbs, Croats and Slovenes - Božidar Jezernik (Łódzkie Studia Etnograficzne, 2019)
Summary: According to Gabriella Elgenius, the societal significance of holidays lies in the preservation of collective memory. Annually repeated shared rituals reinforce the memory of those events and personalities that are expected to be familiar to all the members of the community, in effect pushing all other ones into the shadow of collective forgetting. What is more, the emotionally charged commemorations remind members of the community about their social ties and shared history, reinforcing their national identity. The same process occurred in the newly-formed Kingdom of Serbs, Croats and Slovenes, where the key players exploited national ceremony to implement their (re)interpretations of the past (as the dark age of national dispersion and slavery to foreign masters) and their new agenda for the future. The Unification Day, celebrated on 1 December, as well as the other state holidays, were supposed to contribute to the formation and reinforcement of the narrative image of a community that defined itself as Us and feels like One. The purpose of the Unification Day was to stage national unity and collectively express the will to belong to a firm and lasting community, in order to make sense of the death of past martyrs who gave their lives for Vidovdan ideals. A nation-state cannot exist without national unity. Regretfully, the ruling elites in the Kingdom of Serbs, Croats and Slovenes failed, for various reasons, to nationalise the collective memory of the past and construct an efficient, internalised nationalist ideology. Thus, the Kingdom entered history as the single nation-state without its own nationalism, which meant it was missing the greatest mobilisation force, one that in the modern period has proved itself stronger than geography or religion and more stable than political and economic interests. Even though at the end of the war the citizens of the newly established kingdom were all rooting for Yugoslavia, the new nationstate failed to create the Yugoslavians as a people. It would seem that up until King Alexander’s declaration of dictatorship it had channelled its powers, and even its violence, mostly into the creation of the Serbs.